Manuscript, Philology, and Indonesian Islam - Fachri Aidulsyah; Saiful Hakam (Tashwirul Afkar, 2022)
The manuscript serves as a window into a nation's civilisation. Manuscripts, also known as "Naskah Kuno" or "Naskah Klasik" in the Malay world, have evolved into important pieces of cultural history that need to be conserved. The purpose of the manuscript is to learn about and comprehend the social conditions of the past and to investigate how culture and science are absorbed, recorded, and repeated. Ibn Khaldun (1332-1406) said that science and civilization are products of a variety of factors, including a) the capacity of governments, social structure, and political authority; b) vocations and livelihood opportunities; and c) the development of science and technology.